PROSPEK PERADILAN RESTORATIF BERDASARKAN PANCASILA SEBAGAI SARANA NON PENAL DALAM PENANGGULANGAN DELINKUENSI ANAK DIMASA DATANG - Nur Rochaeti (Faculty of Law, Universitas Diponegoro, 2013)
Children have rights that are specifically different from human rights, and require special treatment and protection, particularly against acts that may harm the development of children, which is a guarantee of legal protection for them as well as any special protection aimed at children committing an offense, and behavioral deviation or also known as